2015
DOI: 10.1007/s10237-015-0655-3
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation instability as a trigger of aneurysm rupture

Abstract: Aneurysm formation and growth is accompanied by microstructural alterations in the arterial wall. Particularly, the loss of elastin may lead to tissue disintegration and appearance of voids or cavities at the micron scale. Unstable growth and coalescence of voids may be a predecessor and trigger for the onset of macroscopic cracks. In the present work, we analyze the instability of membrane (2D) and bulk (3D) voids under hydrostatic tension by using two experimentally calibrated constitutive models of abdomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Damage models can be categorized in 3 groups: (1) deterministic models in which a pseudoelastic strain energy function (SEF) with a few parameters or damage variables of continuum damage mechanics (CDM) is used to characterize the softening/damage effect, either isotropically 19,23 or anisotropically 24-26 ; (2) probabilistic models in which probabilistic damage process and/or fiber recruitment can be included 27,28 ; and (3) microstructural-based damage models of collagen fibers in which the microscopic damage behavior of individual collagen fibrils is considered and homogenized macroscopically. 29 All these formulations can be categorized as nonlocal 4 or local [15][16][17][18][19][20] damage models.…”
Section: Introductionmentioning
confidence: 99%
“…Damage models can be categorized in 3 groups: (1) deterministic models in which a pseudoelastic strain energy function (SEF) with a few parameters or damage variables of continuum damage mechanics (CDM) is used to characterize the softening/damage effect, either isotropically 19,23 or anisotropically 24-26 ; (2) probabilistic models in which probabilistic damage process and/or fiber recruitment can be included 27,28 ; and (3) microstructural-based damage models of collagen fibers in which the microscopic damage behavior of individual collagen fibrils is considered and homogenized macroscopically. 29 All these formulations can be categorized as nonlocal 4 or local [15][16][17][18][19][20] damage models.…”
Section: Introductionmentioning
confidence: 99%
“…2 in which g is the remote hydrostatic tension and A and a are the cavity radii before and after deformation respectively. For the sake of brevity we completely omit the details of analysis that can be found in Volokh (2011) or Volokh (2015.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…For example, it might happen that the ruptured thrombus does not shield stresses anymore which raise in the aneurysmal arterial wall. This stress rise might reach the aneurysmal strength directly or it might trigger a similar cavitation instability mechanism in the aneurysmal wall - Volokh (2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More closely related to the current study is the growing interest in cavitation in soft and biological materials. For example, David and Humphrey [34] studied the stress and strain concentration due to the introduction of a circular hole in an anisotropic bio-tissue, Merodio and Saccomandi [35] studied the effect of fibre-reinforcement in the radial direction, McMahon et al [36] and Pence and Tsai [37][38] investigated cavitation due to growth and swelling, respectively, and Volokh [39] suggested that cavitation instability could be a rational indicator of aneurysm rupture.…”
Section: Introductionmentioning
confidence: 99%